Effects of Implementing Integrated Computer-Assisted Language Learning and Task-Based Learning Activities to Improve Vocational Students’ English Writing - Tongnuan, Kanapod; Sirisrimangkorn, Lawarn (Ratchaphruek Journal, 2024)
The objectives of this study were to examine: 1) the effects of integrated computer-assisted language learning and task-based learning activities on the English writing ability of high vocational certificate students, and 2) students’ satisfaction with learning English through these integrated activities. The population consisted of 42 first-year high vocational certificate students majoring in General Management at a commercial college in Nakhon Ratchasima province. The sample included 22 first-year high vocational certificate students majoring in General Management, selected using the cluster sampling method. The research instruments were lesson plans, an English writing ability test, and a satisfaction questionnaire. Mean scores ( ), standard deviation (S.D.), and t-test were utilized to analyze the data. The results revealed that the mean score of students’ English writing ability in the post-test was significantly higher than in the pre-test at the .05 level. Additionally, the students expressed the highest level of satisfaction with learning English through integrated computer-assisted language learning and task-based learning activities. This indicates that using these integrated learning activities can improve students’ English writing ability.